Human source identification by using a human-associated Escherichia coli genetic marker in the Mae Klong River, Thailand. (21st April 2022) - Nopprapun, Pimchanok; Boontanon, Suwanna Kitpati; Piyaviriyakul, Pitchaya; Sweattatut, Rawiwan; Fujii, Shigeo; Harada, Hidenori
Abstract: Contamination caused by microbial fecal pollution in water bodies is a serious problem in many countries, especially in low- and middle-income countries. Therefore, fecal source tracking is an important method used to understand the source of fecal contamination and to decrease the hazard of waterborne diseases that occurs in the environment. In this study, a human-associated genetic marker for Escherichia coli (H8) was used to investigate the source of fecal contamination in the Mae Klong River, Thailand. Real-time PCR was performed with this marker for 500 E. coli isolates collected from 10 sampling sites along the river, including MK10 (upstream) to MK1 (downstream). The results showed that the proportions of H8-positive isolates were 46, 14, 10, 18, 14, 38, 12, 26, 32, and 14% at MK10–MK1, respectively. All positive proportions were significantly different between the locations ( p < 0.001). The higher occurrence of E. coli with H8 marker detection indicated that domestic wastewater was largely discharged without proper treatment, which is attributable to the high population and the absence of proper sewage treatment in those areas. HIGHLIGHTS: The H8 marker was applied to investigate the human source of fecal pollution in the Mae Klong River, Thailand. High domestic wastewater discharge owing to a high population resulted in higher concentrations of E. coli with the H8 marker detection. In addition to GIS data, fecal source-tracking methods and other information were needed to identify fecal pollution sources. Graphical Abstract